PENGARUH PRESTASI KERJA DAN DISIPLIN TERHADAP PROMOSI JABATAN PADA PEGAWAI KEPOLISIAN KOTA MEDAN - santika bella putri; khamo waruwu (JURNAL MANAJEMEN DAN BISNIS, 2022)
The purpose of this study was to determine the effect of work performance and discipline on the promotion of police officers at the Medan Polrestabes. This research is an associative type of research, where this study seeks to find out the relationship between interrelated variables. This research is located at Polrestabes Medan which is located on Jl. HM. Said No.1, Sidorame Bar. I, District. Medan Perjuangan, Medan City, this research took place from January 2022 to April 2022, the population of this study were all active police employees at the Sabhara Section of Medan Polrestabes totaling 40 employees, the sample used was saturated sampling where all the population of 40 people became the sample , the data analysis technique used in this study is multiple linear regression analysis, while the results of this study are, In this study, achievement assessment has an effect on promotion. It can be seen in column t that the Achievement variable (X1) has a value of tcount (3,672) > ttable ( 2.024) which means Ho is rejected and Ha is accepted. While the significant value of 0.003 is smaller than the probability value of 0.05. In this study, discipline has an effect on promotion. It can be seen in column t that the discipline variable (X2) has a value of tcount (7,113) > ttable (2,024), which means Ho is rejected and Ha is accepted. While the significant value of 0.000 is smaller than the probability value of 0.05. Based on the results of the F test, the data of this study is significant, because Fcount 39,098 > Ftable 3.24, namely Hypotesis a is accepted and Hypotesis o is rejected. The significance level is 0.000 < 0.05.